Analisis Persiapan dan Proses Negosiasi dalam Penyelesaian Konflik Organisasi: Sebuah Kajian Literatur - Fidela Salma Endrista; Remanda Rezki Ramadhani; Ensa Feby Liana; Usna Ma’ul Khasanah; Anang Haris Firmansyah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Conflict is an inseparable part of organizational dynamics, arising from differences in interests, goals, perceptions, and viewpoints among individuals and groups. If not managed effectively, conflict can negatively affect organizational performance and productivity. One approach that can be used to resolve organizational conflicts is through effective negotiation. This study aims to analyze the preparation and negotiation processes in resolving organizational conflicts through a literature review approach. The research employs a qualitative method using a literature review by collecting and analyzing various relevant scientific sources, including books, journal articles, and previous studies. The findings indicate that the success of negotiations is influenced by the parties’ readiness to identify the root causes of problems, establish objectives, gather information, and determine appropriate strategies and alternative solutions. Furthermore, effective negotiation is characterized by open communication, active listening skills, efforts to identify mutual interests, and the achievement of agreements that benefit all parties (win-win solutions). Therefore, thorough preparation and the proper implementation of negotiation processes are essential factors in achieving constructive conflict resolution and supporting the attainment of organizational goals.